Inclusive leadership and employee engagement as critical drivers of sustainability in telecommunication companies - Sulaiman Olusegun Atiku; Kristofine Aili Itembu-Naunyango; Olufemi Michael Oladejo (Administrative Sciences, 2024)
There has been a growing concern about the influence of inclusive leadership on employee engagement in the telecommunications industry. The telecommunications industry is undergoing rapid technological advancements, leading to increased competition and pressure on employees. Creating an inclusive workplace in such a dynamic environment is essential to attracting and retaining talented professionals and driving eco-innovation for sustainable development in Industry 4.0. Despite the importance of inclusive leadership, there is dearth of studies exploring the influence of inclusive leadership on employee engagement in the telecommunications industry. Hence, this study sought to examine the influence of inclusive leadership on employee engagement in selected telecommunication companies in Namibia. A qualitative approach was adopted, where face-to-face interviews were conducted using a semi-structured interview guide. The participants (22 executives) were selected for interviews from two telecommunication companies in Namibia using a purposive sampling method. Data collection involved recording and transcribing participant interviews using Microsoft Word. Thematic analysis was conducted using NVivo 20 software. Results show the importance of empathy and non-hierarchical leadership behaviour as the most critical factor influencing team engagement and discretionary effort in the telecommunications industry in Namibia. Meanwhile, clear career advancement pathways, work autonomy, cross-departmental collaboration, and supervisory support are major contributors to employee engagement for innovative performance and sustainability in the telecommunications industry.
Keywords: 350; employee engagement; equity; diversity; inclusion; inclusive leadership; telecommunicationsindustry